An anatomical study of seasonal dimorphism in the leaves of Phlomis fruticosa - Christodoulakis, N.S. (Annals of Botany, 1989)
Seasonal dimorphism is considered from the anatomical viewpoint. Significant differences can be observed between winter and summer leaves obtained from the same individuals. Winter leaves are thick, amphistomatic with a large number of chloroplasts in the cells of the loose mesophyll. The thinner summer leaves are hairier and hypostomatic, with compact mesophyll and cells that accumulate phenolics and crystals. CbJoroplasts are fewer in number and less developed, and at the ultrastructural level they present pronounced differences from those of the winter leaves. © 1989 Annals of Botany Company.
Keywords: Chloroplast ultrastmcture; Leaf anatomy; Phlomis fruticosa; Seasonal dimorphism